Mechanosensitive ion channels as novel targets in osteoporosis - Beyersdorf, Christoph; Maus, Uwe Martin; Wiedmann, Felix Tobias; Bousch, Juliana Franziska; Waibel, Maximilian; Schmidt, Constanze; Prüser, Merten (Journal of bone and mineral research, 2025)
Osteoporosis is the most prevalent metabolic bone disease globally, leading to an increased risk of fractures. Recent advances in ion channel research have shed light on the importance of mechanosensitive ion channels as novel players in these pathophysiological processes. This perspective discusses the involvement of the mechanosensitive ion channels TREK-1, Piezo, and volume-regulated anion channels (VRACs) as potential novel pharmacological targets for the treatment of osteoporosis. TREK-1, a mechanosensitive K2P channel is important for maintaining the resting membrane potential in many cells, including osteoblasts and osteoclasts. K2P channels regulate osteoblast proliferation and differentiation, as well as osteoclast activity, potentially modulating bone remodeling in osteoporosis. Piezo channels influence osteoblast differentiation and osteoclast activity by modulating calcium influx, which is crucial for osteogenic signaling pathways, such as Wnt/β-catenin and ERK1/2. Piezo1 activation promotes bone formation, while its deficiency leads to impaired osteogenesis and increased bone resorption. Volume-regulated anion channels have been shown to be involved in osteoblast adaptation to mechanical stress and macrophage polarization, which indicates their importance for bone homeostasis. Chronic inflammation is a major contributor to osteoporosis progression. Evidence of ion channel involvement in this process has emerged in recent years. Specifically, macrophage function in osteoporosis seems to be linked to ion channel activity. Inflammatory polarization of macrophages is a key player in inflammation-induced bone loss and can be driven by mechanosensitive ion channels. Modulating these ion channels may provide new therapeutic opportunities. Given the complexity of ion channel interactions in bone cells and their regulatory role in bone remodeling, understanding their precise function in osteoporosis is essential. Targeted modulation of mechanosensitive ion channels holds promise as a novel therapeutic approach to mitigate inflammation-driven bone loss and improve bone density. Further research into their role in osteoclasts and macrophage-driven bone degradation will aid in developing innovative osteoporosis treatments.Osteoporosis is the most common bone disease worldwide. The exact reasons for why bones weaken is often not fully understood, which makes the development of targeted therapies difficult. Our article highlights a new perspective: certain proteins in bone cells, called mechanosensitive ion channels, may be key players in osteoporosis. These channels act like tiny “gates” in the cell membrane that open when cells are stretched, thereby regulating the activity of cells. They help bone cells and immune cells sense their environment and respond to changes. We focus on three groups of these channels: K2P channels influence how bone-building cells (osteoblasts) grow and how immune cells control inflammation. Piezo channels help bone cells sense mechanical forces and control immune cell behavior. Volume-regulated anion channel channels may help bone cells adapt to stress and regulate inflammatory signals. Because of their dual effect on mechanical and inflammatory signaling, changes/alterations in ion channel activity may contribute to bone loss in osteoporosis. Pharmacological targeting of these channels could therefore help to protect bone. Early studies suggest that drugs influencing mechanosensitive ion channels might one day prevent or slow down osteoporosis. More research is needed, but this approach opens exciting new possibilities for treatment.